PENYULUHAN TENTANG PERTUMBUHAN FISIK DAN PERKEMBANGAN MOTORIK ANAK DI KECAMATAN BIRU-BIRU - Fithri Handayani Lubis; Bunga Mari Sembiring; Hengky Frengki Manulang; Herawati Bukit; Friska Ernita Sitorus; Alprindo Sembiring (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The physical and motor development of a child is influenced by many factors, one of which is the labor process. The labor process can be divided into two parts: natural delivery and caesarean section. During spontaneous labor, babies actively experience the labor reflex, but babies born by cesarean section do not experience the labor reflex. Early development of the adult infant brain is influenced by reflex mechanisms, including primitive intrauterine reflexes, birth reflexes, primitive postnatal reflexes, and natural reflexes. Indigenous reflexes, on average, were masked by functional exercise at 6 months of age. Persistent primitive reflexes indicate a developmental disorder. Motor development controls the development of body movements by coordinating the activities of the central nervous system, peripheral nerves, and muscles. This control of movement is due to the development of reflexes that begin in the womb. The development of athletic achievement can be divided into two types. In other words, thorough motor skills and fine motor skills. Overall movement is an aspect of motor (movement) and postural (positional) development, and fine motor skills include mature motor function, good neuromuscular coordination, accurate visual function, and non-verbal intellectual skills.